Governance of Ecosystem Services: A Plea for a New Perspective on Ecosystem Services for Land-use Planners - Gray, Konrad; Savaşçı, Günden; Deppisch, Sonja (European Spatial Research and Policy, 2023)
Integrating the ecosystem services (ES) concept into land-use planning has been the focus of researchers in recent years. Forwarding this objective in order to foster human well-being, urban and regional planning became the focus of research efforts. Furthermore, governance research has been beneficial in studying the coupling of ecosystem services and planning processes. Thus, in this explorative case study we have analysed the governance of urban and regional planning in two case studies – Rostock and Munich – in order to gain insights about the role and value of ecosystem services among planning actors. We conducted semi-structured interviews to identify relevant parameters to facilitate integrational approaches of ecosystem services into decision-making in the context of cross-sectoral urban and regional planning. Based on our results, we argue for a change of the perspective of ES within planning practice. Instead of ecological or economic endeavours, the contribution of ES to human well-being should be in the centre of attention. Human well-being as an overarching aspiration may have the potential to shift ecosystem services from sectoral to cross-sectoral planning.